2019
DOI: 10.1016/j.omtm.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Bridging from Intramuscular to Limb Perfusion Delivery of rAAV: Optimization in a Non-human Primate Study

Abstract: Phase 1 and phase 2 gene therapy trials using intramuscular (IM) administration of a recombinant adeno-associated virus serotype 1 (rAAV1) for replacement of serum alpha-1 antitrypsin (AAT) deficiency have shown long-term (5-year) stable transgene expression at approximately 2% to 3% of therapeutic levels, arguing for the long-term viability of this approach to gene replacement of secreted serum protein deficiencies. However, achieving these levels required 100 IM injections to deliver 135 mL of vector, and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…The level of protein expression is respectively VLP > IM > IAPD ( Table 1 ). 39 As expected, all the animals seroconverted after rAAV administration, as illustrated by detection of anti-AAV1 neutralizing antibodies (NAbs) and immunoglobulin G (IgG) ( Table 2 ). In contrast to results obtained in the phase II AATD clinical trial, these animals showed sporadic and transient elevation in serum creatine kinase or liver transaminases (alanine aminotransferase [ALT]/aspartate aminotransferase [AST]).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…The level of protein expression is respectively VLP > IM > IAPD ( Table 1 ). 39 As expected, all the animals seroconverted after rAAV administration, as illustrated by detection of anti-AAV1 neutralizing antibodies (NAbs) and immunoglobulin G (IgG) ( Table 2 ). In contrast to results obtained in the phase II AATD clinical trial, these animals showed sporadic and transient elevation in serum creatine kinase or liver transaminases (alanine aminotransferase [ALT]/aspartate aminotransferase [AST]).…”
Section: Resultssupporting
confidence: 70%
“…The rhAAT-cMyc fusion protein expression was measured at the mRNA level by qRT-PCR and at the protein level in serum by a semiquantitative immunoblot over time. 39 Our results show that the protein expression was detected in all groups, with a higher protein expression in the VLP group: up to an average of 90 mg/mL at 60 days post-injection. The level of protein expression is respectively VLP > IM > IAPD ( Table 1).…”
Section: Experimental Design Transgene Expression and Cellular Immusupporting
confidence: 48%
See 2 more Smart Citations
“…In comparison to transgenic approaches, like gene knock-out, conditional gene knock-out, or gene-editing by CRISPR/Cas9, the current experimental design is less time consuming as well as less prone to potential off-target effects or developmental failure. Furthermore, using rAAVs for cargo delivery to post-mitotic PHNs supports current ideas [ 43 , 44 , 51 ] to use viral transductions in basic and translational approaches.…”
Section: Discussionsupporting
confidence: 57%